2006
DOI: 10.1002/joc.1338
|View full text |Cite
|
Sign up to set email alerts
|

The development of a new dataset of Spanish Daily Adjusted Temperature Series (SDATS) (1850–2003)

Abstract: Here we present the development of a new adjusted dataset composed of the 22 longest and most reliable Spanish daily temperature records (maximum and minimum temperatures and derived daily mean temperature) covering the period 1850-2003. The paper describes the approaches followed for compiling, controlling the quality and homogenising these 22 daily Spanish records, leading to the creation of a dataset called 'Spanish Daily Adjusted Temperature Series' (SDATS). An assessment of the sources of data and metadat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
1
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(182 citation statements)
references
References 49 publications
9
159
1
9
Order By: Relevance
“…Consistent with Brunet et al (2006), we found 1973 the start year of accelerated warming in Spain and used it as a break point for sub-period comparisons. After that year, positive and negative trenders exhibit different responses to climate in all regions (Fig.…”
Section: Radial Growth Trends and Their Climatic Driverssupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with Brunet et al (2006), we found 1973 the start year of accelerated warming in Spain and used it as a break point for sub-period comparisons. After that year, positive and negative trenders exhibit different responses to climate in all regions (Fig.…”
Section: Radial Growth Trends and Their Climatic Driverssupporting
confidence: 72%
“…The temperature datasets was shortest in SCA but reached the end of the 19th century or beginning of 20th century in the other three regions. We also considered the use of homogenised and adjusted temperature data created for many Spanish meteorological stations (Brunet et al, 2006). Unfortunately, none of these stations were close to our sampling sites and preliminary results showed lower correlations with tree-ring chronologies.…”
Section: Climate Datamentioning
confidence: 99%
“…These checks broadly follow those used by Brunet et al (2006), who implemented the recommendations of Aguilar et al (2003), and were carried out before any corrections were made to the data. This facilitated the cross-checking of flagged values against the original sources as the data were in the same measurement units as the original sources.…”
Section: Quality Control Of the Datamentioning
confidence: 99%
“…[3] Within the last 10 years, many studies, focused on Spanish temperature change on a monthly basis, have shown evidence of warming over the country by analyzing data from groups of stations [e.g., Oñate and Pou, 1996;Esteban-Parra et al, 2003a] or by developing regional time series for peninsular Spain [Brunet et al, 2001a[Brunet et al, , 2001bBrunet et al, 2002;Rodríguez-Puebla et al, 2002;Brunet et al, 2005;Brunet et al, 2006] or for different subregions [Esteban-Parra et al, 1995;Abaurrea et al, 2001;Brunet et al, 2001cBrunet et al, , 2001dGalan et al, 2001;Horcas et al, 2001;Staudt, 2004;Staudt et al, 2005;Morales et al, 2005]. Even though these studies have used different spatial and temporal scales or diverse analytical approaches for assessing data quality and homogeneity, consistent and coherent temporal patterns of warming have been highlighted mainly for the second half of the twentieth century.…”
Section: Introductionmentioning
confidence: 99%
“…The warming has not been equally spread throughout the year, winter recording the greatest rates of change. Finally, the results of the majority of the studies on long-term (twentieth century) Spanish temperature change show that maximum temperature has increased at greater rates than minimum temperature both over the whole mainland Spain [Brunet et al, 2001b;Brunet et al, 2005;Brunet et al, 2006] and over different Spanish subregions: the Middle Ebro River Basin [Abaurrea et al, 2001], Northeastern Spain [Brunet et al, 2001d], the southern Spanish plateau [Galan et al, 2001], the Segura River Basin [Horcas et al, 2001], and the northern Spanish plateau [Morales et al, 2005]. However, different results (i.e., higher rates of change calculated for T min than for T max ) were found by Esteban-Parra et al [2003a], Staudt [2004], and Staudt et al [2005] over mainland Spain and Esteban-Parra et al [1995] over the northern Spanish plateau.…”
Section: Introductionmentioning
confidence: 99%